Study on Chaiyuwendan decoction’s inhibition of hippocampal neuron apoptosis to alleviating depression by activating the AKT/CREB pathway - Zhang, Shaoliang; Cheng, Sijie; Liang, Huiqing; Qiu, Yan; Ren, Jie; Huang, Yv; Zhou, Bangyan; Li, Chunrong; Zhang, Jingmin; Wang, Tianxiang; Wang, Liuyi; Liu, Ruobing; et al. (Frontiers in Pharmacology, 2025)
BackgroundHippocampal neuron damage is closely related to depression, and apoptosis is an important pathway for neuronal damage. Depression belongs to Yubing (depressive disease) in traditional Chinese medicine theory. Chaiyuwendan decoction (CYWD) has significant clinical efficacy in treating depression, however, its specific mechanism is still unclear. This study aims to explore the potential pharmacological active substances and key therapeutic targets of CYWD in treating depression from signaling pathways related with apoptosis.MethodsHPLC-MS method was used to detect the key components of CYWD. The mouse depression model was established by CORT injection. Depressive mice were administered CYWD at low, medium and high doses. Behavioral experiment, neurotransmitters in hippocampus and serum, hippocampal HE staining and Nissl staining were tested in order to evaluate the effects of CYWD in antidepressant and anti nerve damage. The potential targets and signaling pathways for CYWD against depression were predicted through network pharmacology and molecular docking. CORT intervention was used to establish a neuronal apoptosis model of HT22. The effect of CYWD on HT22 were evaluated using CCK-8 proliferation, Nissl staining and apoptotic assays by flow cytometry. According to the predicted results, Western blot and Immunofluorescence assay were used to detect AKT, pAKT, CREB, pCREB and apoptosis-related proteins in hippocampus and HT22 cells.Results134 active components in CYWD were identified, including chlorogenic acid, coumaric acid, rutinoside, naringin, and hesperidin. The in vivo studies showed that CYWD treatment improved mice’ depression-associated behaviors, decreased 5-HT, DA and NE while increased ACTH, reduced hippocampal neuronal damage. Furthermore, the AKT-CREB pathway to inhibit neuronal apoptosis was predicted as the potential key target for CYWD treatment of depression by network pharmacology methods and molecular docking. Subsequently, in vitro and in vivo experiments confirmed that CYWD can inhibit the pro-apoptotic proteins Bax and Caspase 3 by increasing AKT and CREB, and increase anti-apoptotic protein Bcl-2, thereby inhibiting CORT induced apoptosis of mouse hippocampal neurons.ConclusionCYWD can alleviate depression through protecting hippocampal neurons by activating the AKT-CREB signaling pathway, increasing the proportion of anti apoptotic proteins. These findings provided a valuable reference to CYWD as a promising alternative against depression.